2023
DOI: 10.1021/acs.chemmater.3c00054
|View full text |Cite
|
Sign up to set email alerts
|

Two Cu-Based Phosphonate Metal–Organic Frameworks as Efficient Water-Splitting Photocatalysts

Pablo Salcedo-Abraira,
Rubén Serrano-Nieto,
Catalina Biglione
et al.

Abstract: Two novel three-dimensional metal–organic frameworks (MOFs) based on the photoactive pyrene tetraphosphonate ligand and copper (denoted as IEF-8 and IEF-9) have been hydrothermally synthesized and fully characterized (XRD, FTIR, TGA, SEM, XPS, etc.). Their crystal structures were unveiled by single-crystal X-ray diffraction. Remarkably, these materials exhibit coordinatively unsaturated copper (II) sites, free −PO3H2 and −PO3H acidic groups, and good thermal and chemical stability. Further, their optoelectroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 51 publications
(71 reference statements)
0
9
0
Order By: Relevance
“…Moreover, the 3D framework of compound II is well stabilized via intermolecular O–H···O and C–H···O hydrogen-bonding interactions (Table S4 and Figure S4, Supporting Information). From the literature survey, it is found that similar one-dimensional metal–phosphonate chains are often observed with various transition metals, especially the metal centers with octahedral coordination environment. ,, Such one-dimensional Fe, Co, or Ni-phosphonate chains are stabilized in the presence of a templated aliphatic amine. When the metal center is changed from a 3d n -element to 3d 10 -Zn, the coordination environment becomes tetrahedral with three-dimensional zinc phosphonate structures. ,,,, Higher dimensional Zn–phosphonate structures are stabilized with templated linear aliphatic amines or various pyrazine derivatives .…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Moreover, the 3D framework of compound II is well stabilized via intermolecular O–H···O and C–H···O hydrogen-bonding interactions (Table S4 and Figure S4, Supporting Information). From the literature survey, it is found that similar one-dimensional metal–phosphonate chains are often observed with various transition metals, especially the metal centers with octahedral coordination environment. ,, Such one-dimensional Fe, Co, or Ni-phosphonate chains are stabilized in the presence of a templated aliphatic amine. When the metal center is changed from a 3d n -element to 3d 10 -Zn, the coordination environment becomes tetrahedral with three-dimensional zinc phosphonate structures. ,,,, Higher dimensional Zn–phosphonate structures are stabilized with templated linear aliphatic amines or various pyrazine derivatives .…”
Section: Resultsmentioning
confidence: 94%
“…From the literature survey, it is found that similar one-dimensional metal–phosphonate chains are often observed with various transition metals, especially the metal centers with octahedral coordination environment. ,, Such one-dimensional Fe, Co, or Ni-phosphonate chains are stabilized in the presence of a templated aliphatic amine. When the metal center is changed from a 3d n -element to 3d 10 -Zn, the coordination environment becomes tetrahedral with three-dimensional zinc phosphonate structures. ,,,, Higher dimensional Zn–phosphonate structures are stabilized with templated linear aliphatic amines or various pyrazine derivatives . If the amine molecules are modified from aliphatic to aromatic amines, the nitrogen atoms intend to bind with the metal centers to improve the dimensionality .…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Applying molecular precursors to prepare structure-controlled catalysts with homogeneously dispersed catalytic species on the support is a well-known and widely used method. However, there is a lack of information on applying phosphorus-containing metal complexes (phosphates, phosphonates, and phosphinates) as precursors to nonoxidative ethanol dehydrogenation catalysts. Numerous studies have been conducted on copper phosphates and phosphonates. However, the application of phosphinate ligands for the formation of copper complexes has seen limited exploration, with a modest number of copper complexes based on phosphinate ligands present to date. A small amount of the copper complexes with macrocyclic ligands possessing pendant phosphinate groups are also being studied for potential medical applications. The formation of insoluble polymeric compounds is commonplace in such systems, which is a factor that limits their potential application as molecular precursors. Typical strategies employed for the isolation of molecular species include the utilization of bulky ligands, ,…”
Section: Introductionmentioning
confidence: 99%